Peran Orang Tua Terhadap Pembinaan Anak Bermasalah di Kelurahan Maricayakota Makassar - Irvan; Sakaruddin Mandjarreki (Universitas Islam Negeri Alauddin Makassar, 2022)
The role of parents in fostering children is very important in building a sakinah household. The type of research used is descriptive qualitative research. The approach used is a social welfare approach and a sociological approach. Sources of data in this study are parents, children and village officials. The method used in data collection is the method of observation, interviews and documentation. The research instruments used were interview guides, cameras, recording devices, and notebooks. Data processing techniques from all sources obtained. The data analysis technique used is qualitative analysis which is a continuous and repeated effort, the data obtained in the field is processed with the intention of providing information. The results showed that, the efforts made by parents in fostering problem children in Maricaya Baru Village, Makassar District were carried out by giving children a supportive environment at home, giving children enthusiasm in living life, discussing children's problems together, supervising children's activities, balancing attitudes when advise children. The causes of problem children in Maricaya Baru Village from internal factors are biological factors, psychological factors, economic factors, while external factors are educational factors, social factors, lack of communication factors, lack of supervision and environmental factors.